Preparação e caracterização de nanocompósitos estruturais baseados em poli(3-hidroxibutirato-co-hidroxivalerato) e nanopartículas de dióxido de titânio para o emprego em engenharia tecidual - Braga, Natalia Ferreira [UNIFESP] (2015)
Preparation and characterization of structural nanocomposites based on poly (3-hydroxybutyrate-co-hydroxyvalerate) and titanium dioxide nanoparticles for use in tissue engineering In this work it was developed nanocomposites based on poly (3-hydroxybutyrate-co-hydroxyvalerate) (PHBV) and titanium dioxide (TiO2), by means of three different techniques: casting, electrospinning, and spin-coating. Therefore, the TiO2 nanoparticles were synthesized by hydrothermal treatment of PCT gel (titanium peroxo complex). The nanoparticles had a rod format with average diameter of 12 nm and an average length of 40 nm with predominantly of rutile crystallographic phase. Subsequently, PHBV nanocomposites were prepared with different proportions of TiO2 nanoparticles (1%, 2.5% and 5% w/w) and compared with the neat polymer as its physical-chemical and thermal properties. In general, the nanoparticles catalyzed the process of biodegradation and photo-degradation of the PHBV polymer matrix. DSC analysis showed that the Tg of the material decreases with the inclusion of TiO2 and by TGA revealed that the degradation temperature is smaller in nanocomposites compared to pure polymer. While, DMA analysis indicated that there was an increase in the damping properties of the nanocomposites compared to PHBV. Finally, mats were prepared by electrospinning to verify cell viability of the nanocomposites. SEM analyzes showed the formation of interconnected continuous fibers, so candidates for use in tissue engineering. Thus, the study of cell viability was conducted in the nanocomposites, which showed that the cells growth on PHBV mats showed good cell adhesion and proliferation rate and, in general, treatment with TiO2 increased cell growth. Membranes prepared by spin-coating technique showed very thin thickness that ranged from 3.8 ?m to 9.1 ?m.